2023
DOI: 10.3389/fmicb.2023.1272754
|View full text |Cite
|
Sign up to set email alerts
|

Comparing technology and regulatory landscape of probiotics as food, dietary supplements and live biotherapeutics

Irina Spacova,
Sylvie Binda,
Jessica Anne ter Haar
et al.

Abstract: Application of beneficial microorganisms as probiotics targets a broad range of intended uses, from maintaining health and supporting normal bodily functions to curing and preventing diseases. Currently, three main regulatory fields of probiotic products can be defined depending on their intended use: the more similar probiotic foods and probiotic dietary supplements, and live biotherapeutic products. However, it is not always straightforward to classify a probiotic product into one of these categories. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…In Europe, the regulatory framework for probiotics has been criticized for failing consumers and the industry by restraining key information on scientifically backed products and impeding market growth. The situation in the EU is not currently harmonized, with different member states taking different approaches to the regulation of probiotics [ 47 ]. In the US, the registration of probiotics is regulated by the Federal Food, Drug, and Cosmetics Act (FFDCA) [ 48 ].…”
Section: Production Challenges For the Ngpsmentioning
confidence: 99%
“…In Europe, the regulatory framework for probiotics has been criticized for failing consumers and the industry by restraining key information on scientifically backed products and impeding market growth. The situation in the EU is not currently harmonized, with different member states taking different approaches to the regulation of probiotics [ 47 ]. In the US, the registration of probiotics is regulated by the Federal Food, Drug, and Cosmetics Act (FFDCA) [ 48 ].…”
Section: Production Challenges For the Ngpsmentioning
confidence: 99%
“…A recent study showed that in adults diagnosed with MDD and with an incomplete response to prescription antidepressants a supplementation with a 14-strain blend probiotic resulted in a greater improvement compared to those on placebo [127]. Given the expanding horizon of probiotic research, it is crucial to distinguish probiotics used as food supplements from the LBPs aimed to be used in patients [125,128]. As evidence grows supporting the role of probiotics in treating, not just preventing, specific CNS diseases, the conversation around developing bacteria as medicines rather than preventive measures gains even more relevance.…”
Section: Psychobiotics As Prevention Versus Treatmentmentioning
confidence: 99%
“…For probiotic‐based dietary supplements, safety evaluation includes assessing their potential to cause adverse effects such as infections, allergic reactions or gastrointestinal disturbances, particularly in vulnerable populations such as infants, elderly individuals or immunocompromised individuals. Probiotic products intended for human consumption are subject to regulatory oversight in many countries, establishing guidelines and standards relative to strain characterization, labelling, manufacturing practices and quality control measures aimed to ensure product safety and efficacy (Spacova et al., 2023 ). Clinical studies have been conducted to evaluate the tolerance, adverse effects, microbial stability and the impact of probiotics on host physiology and microbiota composition, and probiotic manufacturers are requested to implement stringent quality control measures throughout the production process to ensure product consistency and purity (Huys et al., 2013 ; Kolacek et al., 2017 ; Spacova et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotic products intended for human consumption are subject to regulatory oversight in many countries, establishing guidelines and standards relative to strain characterization, labelling, manufacturing practices and quality control measures aimed to ensure product safety and efficacy (Spacova et al., 2023 ). Clinical studies have been conducted to evaluate the tolerance, adverse effects, microbial stability and the impact of probiotics on host physiology and microbiota composition, and probiotic manufacturers are requested to implement stringent quality control measures throughout the production process to ensure product consistency and purity (Huys et al., 2013 ; Kolacek et al., 2017 ; Spacova et al., 2023 ). For environmental applications of probiotics, such as remediation or agricultural use, risk assessments should also include the evaluation of probiotics' potential to disrupt natural microbial communities, accumulate in the environment and introduce novel genetic material (Lensch et al., 2024 ).…”
Section: Introductionmentioning
confidence: 99%